Anaphylaxis in Risky Populations - Beyaz, Şengül; Gelincik, Aslı (Current Pharmaceutical Design, 2023)
Anaphylaxis should be clinically diagnosed with immediate recognition, whereas, despite advances in the field of allergy, the symptoms of anaphylaxis remain to be under-recognized, diagnosis is often missed, and treatment is often delayed. Anaphylaxis presents with symptoms in a spectrum of severity, ranging from mild objective breathing problems to circulatory shock and/or collapse. Indeed, anaphylaxis management frequently relies on a ‘one-size-fits-all approach’ rather than a precision medicine care model, despite the evidence that anaphylaxis is a heterogeneous condition with differences in causative agents, clinical presentation, and host susceptibility. The key important risk factors for severe anaphylaxis and mortality are certain age groups or certain stages of life (infants, elderly and pregnant women), augmenting factors (physical exercise, alcohol consumption, menstruation, acute infections), concurrent use of some medications (beta-adrenergic blockers (β-blockers) and angiotensin-converting enzyme (ACE) inhibitors, non-steroidal anti-inflammatory drugs (NSAIDs), and proton pump inhibitors (PPIs), and concomitant diseases (i.e. asthma, cardiovascular disease, mastocytosis). The present review aims to collectively address the patient groups who are at high risk of having anaphylaxis, those who have a more severe course, those that are difficult to diagnose, and require a special approach in treatment. Therefore, the risky populations like the elderly, pregnant women, patients receiving β- blockers or ACE inhibitors, those with concomitant cardiovascular diseases, asthma, and mastocytosis, or those having higher baseline serum tryptase levels are discussed, including their clinical presentations and treatment strategies. Additionally, anaphylaxis during the perioperative period is addressed.
Keywords: cardiovascular diseases